1989
DOI: 10.1002/cne.902860211
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution and partial characterization of FLFQPQRFamidelike peptides in the central nervous system of rats

Abstract: Two peptides that are structurally related to the molluscan tetrapeptide Phe-Met-Arg-Phe-NH2 (FMRF-NH2) were recently isolated from bovine brain extract (Yang et al.: Proc. Natl. Acad. Sci. USA 82:7757-7761, '85). These peptides have an attenuating effect on morphine-induced analgesia when injected intracerebroventricularly in rats. Antisera against the two peptides--an octapeptide, Phe-Leu-Phe-Gln-Pro-Gln-Arg-Phe-NH2 (F8F-NH2), and an octadecapeptide, Ala-Gly-Glu-Gly-Leu-Ser-Ser-Pro-Phe-Trp-Ser-Leu-Ala-Ala-Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 37 publications
4
57
1
Order By: Relevance
“…The localization of mRNA and binding sites for NPFF1 and NPFF2 in various components of the basal ganglia, such as the nucleus accumbens, substantia nigra, and the caudate putamen, suggests that NPFF receptors might play an in the regulation of the central dopaminergic system, albeit and indirect one, because previous studies have shown that NPFF binding sites are not found in dopaminergic cell bodies (36). Some of the highest levels of NPFF-like immunoreactivity have been observed in the rat hypothalamus (3,37). The localization of NPFF2 receptor binding sites and NPFF2 mRNA in the hypothalamus, a region involved in catecholaminergic and serotonergic feeding systems, circadian feeding, and spontaneous activity, suggests that NPFF2 may be involved in the regulation of ingestive behavior.…”
Section: Localization Of Npff1 and Npff2 Mrna In Human Andmentioning
confidence: 99%
“…The localization of mRNA and binding sites for NPFF1 and NPFF2 in various components of the basal ganglia, such as the nucleus accumbens, substantia nigra, and the caudate putamen, suggests that NPFF receptors might play an in the regulation of the central dopaminergic system, albeit and indirect one, because previous studies have shown that NPFF binding sites are not found in dopaminergic cell bodies (36). Some of the highest levels of NPFF-like immunoreactivity have been observed in the rat hypothalamus (3,37). The localization of NPFF2 receptor binding sites and NPFF2 mRNA in the hypothalamus, a region involved in catecholaminergic and serotonergic feeding systems, circadian feeding, and spontaneous activity, suggests that NPFF2 may be involved in the regulation of ingestive behavior.…”
Section: Localization Of Npff1 and Npff2 Mrna In Human Andmentioning
confidence: 99%
“…The major population of NPFF-expressing neurons in the rat brain lies within the nucleus of the tractus solitarius (NTS; Kivipelto et al 1989, Boersma et al 1993, Lee et al 1993, Vilim et al 1999) and projects to the ventral lateral medulla (VLM), lateral parabrachial nucleus (lPBN) and paraventricular nucleus of the hypothalamus (PVN; Jhamandas et al 2001, Goncharuk et al 2006. NPFF-expressing neurons have also been reported in the vicinity of the ventromedial (VMN) and dorsomedial (DMN) nuclei of the hypothalamus.…”
Section: Npff Familymentioning
confidence: 99%
“…The chemical structural resemblance (ArgPhe-amide) between FMRFa-like peptides and g-MSHs, their comparable haemodynamic pro®le (increase in MAP and HR) (Allard et al, 1995;Barnard & Dockray, 1984a;De Wildt et al, 1993;Mues et al, 1982;Thiemermann et al, 1991;Wong et al, 1985) and correspondent anatomical location of these peptides and their receptors within the brain (hypothalamus and nucleus tractus solitarius) (Fodor et al, 1996;Kivipelto et al, 1989;Majane et al, 1989;O'Donohue et al, 1984;Pittius et al, 1984), makes the FMRFa/NPFFa/MERFa receptor a very important candidate for mediating the cardiovascular e ects of g-MSHs. Therefore, in the present study various peptides with a Cterminal Arg-Phe structure are tested for their haemodynamic pro®le in conscious rats.…”
Section: Introductionmentioning
confidence: 99%